Pengembangan Gim Edukasi Mengenai Virus Menggunakan Teknologi Augmented Reality - Hrizto Hanie Del Piero; Tri Afirianto; Wibisono Sukmo Wardhono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Each individual learning method has a different concept, related to this learning media also has an important role with the learning process. Quality education can only be realized if supported by quality learning, so that all factors will be supporting in the aspect of education, in this case can be exemplified as Augmented Reality (AR) technology which is one of the merging technologies between the concepts of 2D objects or 3D objects to be applied in environments that model virtual objects in a real state of time. According to research on game education produces that one of the learning media or modeling learning concepts in one of the techniques is to use Education Game. Associated with the study stated that learning conducted by class X students has learning constraints when memorizing Biology material. The memorization of the Biology class X class is stated in internal factors during the process of teaching and learning activities. Several other internal factors are related to students' interest in conducting the learning process, so an external factor is needed as a support for learning in the form of Student learning tools. This learning tool can be implemented in the Education Game using Iterative Rapid Prototyping, which is a method that supports the design of an iteration system, so that the needs implemented in the system will be in accordance with the definition of needs to meet the wishes of the players. This research experienced three iterations in the design phase and two iterations in the implementation phase. The testing phase in this study uses SUS (System Usability Scale) to test interface interactions in the game. Based on a value of 73,25 that has been obtained, it was concluded that the virus classification education game application is easy to use by users.